HAKIKAT TUJUAN PENDIDIKAN ISLAM - Abdul Wahab Syakhrani; Akhmad Syahbudin (Borneo : Journal of Islamic Studies, 2020)
The essence of the purpose of Islamic education is inseparable from the values related to Islam which are guided by the al-Qur'an and Hadith. This study is a literature study by examining the nature of the objectives of Islamic education. The research findings indicate that; First, the philosophy of Islamic education is inseparable from the study of the al-Qur'an and hadith. However, the impact of social changes experienced by humans has had an impact on all fields, including in education. Al-Qur'an and hadith which were originally used as evidence for Islamic education are in fact only memories. Second, views regarding the nature, purpose, and usefulness of Islamic education will go hand in hand in accordance with the guidelines and views of the Qur'an. If associated with educators, the results of their education can produce positive morals.